Age and gender interactions in ultraendurance performance: Insight from the triathlon - Lepers, R.; Maffiuletti, N. A. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The purposes of this study were (i) to investigate the effect of age on gender difference in Hawaii Ironman triathlon performance time and (ii) to compare the gender difference among swimming (3.8 km), cycling (180 km), and running (42 km) performances as a function of age.